A Study of Shigellosis Bacteria disease Model with Awareness Effects - Jasim, Watheq Ibrahim; AL-Husseiny, Hassan Fadhil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
In this paper, a mathematical model is proposed and studied to describe the spread of shigellosis disease in the population community. We consider it divided into four classes namely: the 1st class consists of unaware susceptible individuals, 2nd class of infected individuals, 3rd class of aware susceptible individuals and 4th class are people carrying bacteria. The solution existence, uniqueness as well as bounded-ness are discussed for the shigellosis model proposed. Also, the stability analysis has been conducted for all possible equilibrium points. Finally the proposed model is studied numerically to prove the analytic results and discussing the effects of the external sources for disease and media coverage on the dynamical behaviors of shigellosis disease.